Narrative Economics and Intersubjective Fiction: The Construction of Bitcoin Finfluencer Discourse on YouTube Social Media in Indonesia - Deri Hudaya; Haryadi Mujianto; Muhamad Hilman Firmansyah (Universitas Tribhuwana Tungga Dewi, 2026)
This study analyzes the narrative construction of Bitcoin on Angga Andinata's YouTube channel through two sample videos representing opposing market phases: Halving 2024: Ini Jalan Ninjaku (bull market phase) and Bocoran Bottom Bitcoin 2026 (bear market phase). Integrating Yuval Noah Harari's theory of intersubjective fiction, John Searle's institutional facts, Robert Shiller's narrative economics, and Robert Stanton's structuralism, this qualitative study aims to reveal how Bitcoin is constructed as a collective belief system in Indonesia. Data were collected through the documentation of verbal transcripts and screenshots of visual elements. The findings indicate that Bitcoin is constructed as a protagonist character (